Intervening Effects of Total Alkaloids of Corydalis saxicola Bunting on Rats With Antibiotic-Induced Gut Microbiota Dysbiosis Based on 16S rRNA Gene Sequencing and Untargeted Metabolomics Analyses - Liu, Xi; Zheng, Hua; Lu, Rigang; Huang, Huimin; Zhu, Hongjia; Yin, Chunli; Mo, Yiyi; Wu, Jinxia; Liu, Xuwen; Deng, Ming; Li, Danfeng; Cheng, Bang; et al. (Frontiers in Microbiology, 2019)
Gut microbiota dysbiosis induced by antibiotics was strongly connected with health concerns. Studying the developmental mechanism of antibiotics-induced gut microbiota dysbiosis could help exploit effective drugs and prevent these serious diseases. Here, urinary and fecal biochemical changes and cecum microbial diversity in antibiotics-induced gut microbiota dysbiosis rats with TACS treatment were investigated by 16S rRNA gene sequencing analysis and untargeted metabolomics. Results of microbial diversity showed that ten kinds of microbiota in genera level could be disturbed by antibiotics and two of them were back-regulated by TACS. Untargeted metabolomics study found 34 potential biomarkers in urine and feces may be the most related metabolites in development and TACS treatment of antibiotics-induce gut microbiota dysbiosis, which involved in six metabolic pathways including branched-chain amino acids metabolism, bile acids metabolism, arginine and proline metabolism, purine metabolism, aromatic amino acid metabolism and amino sugar and nucleotide sugar metabolism. Notably, there was a strong correlation between those metabolic pathways and two gut microbiota genera (blautia and intestinibacter) by means of correlation analysis, which suggested that TACS might synergistically mediate four metabolic pathways including branched-chain amino acids metabolism, bile acids metabolism, arginine and proline metabolism and purine metabolism to modulate the gut microbiota dysbiosis. Furthermore, we perform molecular docking to simulate the high-precision docking and molecular pathway maps to illuminate the way ligands act on complex molecular network. This work provides a comprehensive understanding of the protective effects of TACS on the host metabolic phenotype and intestinal microbiome in gut microbiota dysbiosis rats, and presents a new insight into the discovery of effectively drug and advisable therapeutic method.